Documentation of Vertical Connectors Between Successive Drums in Ancient Columns-Literature and In-Situ Investigation - Vasiliki Palieraki; Eleni Tavouktsi; Eleni Karakike; Constantinos Arvanitis (Heritage)
The current paper is dedicated to the documentation of the characteristics of vertical connectors (gomfoi) in ancient columns and to the observed pathology. The gathering of the relative information aims to provide the data necessary for decisions related to an experimental program, investigating the behaviour of columns provided with connectors between successive drums. The investigation has been carried out in monuments where the use of connectors is already known, as well as in monuments for which there is insufficient information. Monuments for which it is assumed that there are no connectors have also been studied to confirm the hypothesis. Literature review, in situ observation, and the application of non-destructive investigation methods (geo-radar) have led to the documentation of the use and location of connectors in the monuments under study.